Pulsed Electromagnetic Field Therapy as a Complementary Alternative for Chronic Pelvic Pain Management in an Interstitial Cystitis/Bladder Pain Syndrome Patient - Tyler L. Overholt; Christina Ross; Robert J. Evans; Stephen J. Walker (Case Reports in Urology)
Interstitial cystitis/bladder pain syndrome is a chronic pelvic pain condition with no known etiology that affects millions of women and men in the United States. Current management can be aggressive for individuals who are refractory to less invasive options, often resulting in the use of opioid narcotics and/or surgical procedures under general anesthesia, with higher risks and side effects to patients. Pulsed electromagnetic field therapy is a noninvasive therapeutic strategy that is thought to reduce inflammation and pain via alteration of cellular function and microcirculation. This therapy has demonstrated efficacy in management of other chronic pain syndromes including fibromyalgia and chronic low back pain. Herein, we describe a case of pulsed electromagnetic field therapy for management of interstitial cystitis/bladder pain syndrome that resulted in decreases in pelvic pain, burning with bladder filling, and other nonpelvic pain symptoms. This case provides support for a formal clinical trial to evaluate the efficacy of pulsed electromagnetic field therapy for the management of chronic pelvic pain in interstitial cystitis/bladder pain syndrome.